Salivary alterations in type 2 (non-insulin-dependent) diabetes mellitus and hypertension - Dodds MWJ, Yeh C-K, Johnson DA (Blackwell Synergy, 2000)
The aim of this study was to determine whether saliva output and composition are altered in type 2 diabetes mellitus by comparison with a healthy, non-medicated control group, and also a group of hypertensives. Methods: From a community-dwelling cohort of Mexican American and European American subjects enrolled in the OH:SALSA oral aging study, we identified 233 subjects with type 2 diabetes mellitus, 227 with hypertension, and 240 healthy control subjects. We collected unstimulated whole (UW) and submandibular/ sublingual (US) saliva, as well as stimulated parotid (SP) and submandibular/ sublingual (SS) saliva.